2020
DOI: 10.21203/rs.2.23795/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association of DNA repair gene variants with colorectal cancer: risk, toxicity, and survival

Abstract: Background: Single nucleotide polymorphisms (SNPs) in DNA repair genes have a potential clinical value in predicting treatment outcomes. In the current study, we examined the association of SNPs in the genes XRCC1-rs25487, ERCC1-rs11615, ERCC2-rs238406, and ERCC2-rs13181 with colorectal cancer (CRC) risk, relapse-free survival (RFS), overall survival (OS), and toxicity during chemotherapy.Methods: SNPs were analysed in 590 CRC cases and 300 controls using TaqMan technology. The association of SNPs with CRC ris… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The outcomes of some investigation about the association of XRCC1 (rs25487) polymorphism with colorectal cancer risk have been contradictory. For example, two recent studies indicated association with increased risk of colorectal cancer (Karam et al, 2016;Abu Halim et al, 2016), while a case-control study in Sweden found no association with CRC risk (Salimzadeh et al, 2020). Also, other findings about the association of OGG1 (rs1052133) polymorphism with susceptibility to CRC remain controversial (Lai et al, 2016;Zou et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The outcomes of some investigation about the association of XRCC1 (rs25487) polymorphism with colorectal cancer risk have been contradictory. For example, two recent studies indicated association with increased risk of colorectal cancer (Karam et al, 2016;Abu Halim et al, 2016), while a case-control study in Sweden found no association with CRC risk (Salimzadeh et al, 2020). Also, other findings about the association of OGG1 (rs1052133) polymorphism with susceptibility to CRC remain controversial (Lai et al, 2016;Zou et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The excision repair cross-complementation 3 (ERCC3) gene encodes a DNA helicase that plays an important role in nucleotide excision repair. The polymorphisms of ERCC3 have been reported to be associated with several cancers, such as colorectal cancer, pancreatic cancer, breast cancer, and OS (5,31,32). The potential mechanism of OS susceptibility was deemed to be its functions as rate-limiting enzymes in the NER pathway (33).…”
Section: Discussionmentioning
confidence: 99%